Association between placental vitamin D receptor expression and cord blood vitamin D level and its effect on the birth weight of newborns - Sathish, Paulraj; Raveendran, Sajeethakumari; Padma, Ramasamy; Balakrishnan, Doraisami; Muthusami, Muthulakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Vitamin D deficiency during pregnancy affects fetal growth and development. The present study explored the association between vitamin D levels in cord blood and placental vitamin D receptor expression. Methods: A total of 54 subjects with live-born singleton deliveries were included in SRM Medical College Hospital and Research Centre, Kattankulathur, India. Cord blood and placenta was obtained at the time of delivery. Results: The mean newborn vitamin D level was 20.07 ng/mL (13-27.50). The mean of relative vitamin D receptor (VDR) expression was 1.45Ct (range 0.10-2.6). Mean comparison of cord serum 25(OH) D3 and VDR revealed significant at p<0.05 by student’s t-test. The newborn anthropometric measurement of head circumference 31.44±3.99 cm, Chest circumference 28.88±4.30 cm, Body length 45.52±8.05 cm, Birth weight 2660.61±353.27 g had significant association with mean VDR expression at p <0.05 level by student t-test analysis. Further, Pearson correlation coefficient also revealed strong positive correlation of placental VDR and cord serum vitamin D (r=0.853, p <0.05). Conclusions: The present study indicates that there was a high prevalence of vitamin D deficiency in the south Indian newborns and the study suggested that VDR had crucial role in maternal to fetal nutrient transfer mechanism. Vitamin D status in cord blood is associated with the birth weight of newborns. Hence, Vitamin D levels during gestation may affect fetal growth and development.